2018
DOI: 10.1038/s41572-018-0001-z
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis

Abstract: Atopic dermatitis (AD) is the most common chronic inflammatory skin disease, with a lifetime prevalence of up to 20% and substantial effects on quality of life. AD is characterized by intense itch, recurrent eczematous lesions and a fluctuating course. AD has a strong heritability component and is closely related to and commonly co-occurs with other atopic diseases (such as asthma and allergic rhinitis). Several pathophysiological mechanisms contribute to AD aetiology and clinical manifestations. Impairment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
1,186
0
57

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,231 publications
(1,358 citation statements)
references
References 227 publications
12
1,186
0
57
Order By: Relevance
“…Though the prevalence of atopic dermatitis (AD) is highest in childhood, the chronic nature of the disease imposes a burden to the patient and society also in adulthood. Recent studies report a prevalence of 6–10%, in adults, which is higher than previously reported . Furthermore, a Danish study found persistent AD in 50% of an adult population diagnosed with AD in school age .…”
Section: Introductionmentioning
confidence: 71%
“…Though the prevalence of atopic dermatitis (AD) is highest in childhood, the chronic nature of the disease imposes a burden to the patient and society also in adulthood. Recent studies report a prevalence of 6–10%, in adults, which is higher than previously reported . Furthermore, a Danish study found persistent AD in 50% of an adult population diagnosed with AD in school age .…”
Section: Introductionmentioning
confidence: 71%
“…[1][2][3][4][5][6][7][8][9][10] The disease itself is not new, and descriptions can be found in ancient medical literature 11,12 with Emperor dermatologic descriptions in the 19th century, it became a clearcut entity in the 20th century, 11,12 especially when its prevalence started to increase in the last decades of the 20th century. [1][2][3][4][5][6][7][8][9][10] The disease itself is not new, and descriptions can be found in ancient medical literature 11,12 with Emperor dermatologic descriptions in the 19th century, it became a clearcut entity in the 20th century, 11,12 especially when its prevalence started to increase in the last decades of the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that dysbiosis of the skin microbiota and colonization by Staphylococcus aureus are common in AD . However, the exact mechanism of skin microbiota involvement in AD patients is not clear.…”
Section: Importance Of Exosomes In Chronic Inflammatory Skin Diseasesmentioning
confidence: 99%